A Case Series of Very Late-onset Schizophrenia-like Psychosis: Is It a Dimension of Dementia?. Issue 6 (November 2021) - Zazaian, Danielle; Gifford, Lindsey; Rath, Swapnil
Abstract : Background: Emerging research has shown that there may be a subset of patients who develop a first-break psychosis later in life when they are over 60 years of age. Very late-onset schizophrenia-like psychosis (VLOSLP) differs from early-onset schizophrenia in a few very important ways that lead us to believe that there may be a distinct pathologic process involved. Methods: We present 4 cases of females with psychotic symptoms that first appeared after the patients were 60 years of age. We conducted a literature review and found that our older adult psychiatric unit is not alone in struggling with diagnoses for these individuals. Results: Some of these patients have a disease that will progress to a neurocognitive disorder, but a large group of others will remain cognitively intact. Fortunately, the treatment for both processes is very similar, but studies have shown that patients with VLOSLP will need significantly lower doses of antipsychotics compared with those with early-onset schizophrenia. Conclusions: It remains unclear if VLOSLP is a unique disorder, a prodrome to dementia, or a different condition that is not yet understood. Further research is needed to develop comprehensive treatment for patients with VLOSLP.